Determinants of Impulse Buying Through Positive Emotion at the Oh! Some - Sri Murtiasih; Aqila Putri; Irwandaru Dananjaya (Return : Study of Management, Economic and Bussines, 2025)
In the era of globalization and increasingly fierce retail business competition, retail stores need to create an attractive shopping experience for consumers to increase competitiveness. OH! SOME retail store as one of the modern retail stores implements store atmosphere, visual merchandising, and product diversity strategies to attract consumer attention and encourage impulse buying behavior. This study aims to analyze the influence of factors that can affect impulse buying through positive emotions. This study aims to find out and analyze the influence of store atmosphere, visual merchandising and product diversity on impulse buying through positive emotions in OH! SOME. This study is primary data with the test stage being carried out is a measurement model (outer model) consisting of validity test (convergent validity and discriminant validity) and reliability test (composite reliability and Cronbach's alpha and structural model (inner model) consisting of R-square (R2), Predictive relevance (Q2), F-square (f2) and hypothesis testing: path coefficient consisting of direct effect and indirect effect. Data was collected using questionnaire instruments and valid data from 150 respondents with the criteria of gen z consumers aged 18-27 and had made purchases at OH! SOME at least 1 time. The sampling method uses non-probability sampling with purposive sampling techniques. The tool used is SMART PLS. The results showed that partially the variables Store Atmosphere, Visual Merchandising, and Product Diversity had an effect on Impulse Buying and Positive Emotion, but Positive Emotion was only able to mediate the variables of Visual Merchandising and Product Diversity on Impulse Buying in OH! SOME.